P232 Once-daily co-administration of glycopyrronium and indacaterol via Breezhaler® device improves lung function and symptoms in patients with COPD versus indacaterol alone: the GLOW6 study. (14th November 2013) - Vincken, W; Aumann, J; Jack, D; Chen, H; Henley, M; Goyal, P
Abstract : Introduction: To benefit symptomatic patients with moderate-to-severe COPD not managed by single bronchodilator, COPD management strategies recommend combining bronchodilators with different mechanisms. We compared, once-daily dual bronchodilation by co-administration of the long-acting muscarinic antagonist (LAMA) glycopyrronium 50µg (GLY) and the long-acting β2- agonist (LABA) indacaterol 150µg (IND), with IND 150 µg monotherapy. Methods: In this randomised, multicentre, placebo-controlled, double-blind, parallel-group study, patients with moderate-to-severe COPD were administered with GLY + IND or IND + placebo (1:1; all delivered via Breezhaler ® device) for 12 weeks. We assessed lung function, dyspnoea (via the transition dyspnoea index [TDI]), patient-reported symptoms, and safety and tolerability over 12 weeks. Results: Of the 449 patients randomised (GLY + IND [n = 226]; IND [n = 223]), 94.0% completed the study. At Week12, GLY + IND demonstrated a statistically significant improvement in mean trough forced expiratory volume in one second (FEV1 )over IND (least squares mean treatment difference [Td]: 64 mL; p < 0.001). Significantly greater improvements in FEV1 area under curve from 30 min to 4h (FEV1 AUC30min-4h ) and trough forced vital capacity were observed with GLY + IND vs IND on Day1 (Td: 105 mL, 112 mL, respectively) and at Week12 (Td: 111 mL, 93 mL, respectively), all p < 0.01. GLY + IND demonstrated significant improvements in inspiratory capacity versus IND at most timepoints on Day1 and Week12 (Td: 59 to 159 mL). GLY + IND significantly improved TDI total score versus IND (Td: 0.49, p = 0.037) and a higher proportion of patients on GLY + IND achieved a clinically meaningful improvement (≥1 point) versus IND at Week12 (odds ratio 1.97 favouring GLY + IND; p = 0.004). GLY + IND was also associated with significantly greater improvements in mean daytime respiratory symptom score and the percentage of days being able to perform usual daily activities vs IND over 12 weeks of treatment (Td: -0.1 and 6.2, respectively; both p < 0.05). The overall incidence of adverse events (AEs) and serious AEs (SAEs) was comparable for the GLY + IND and IND groups (AEs: 37.6% vs 34.1%; SAEs: 2.2% vs 2.3%, respectively). Conclusion: In patients with moderate-to-severe COPD, compared with indacaterol monotherapy, once-daily co-administration of glycopyrronium and indacaterol delivered via Breezhaler ® device provided superior improvements lung function and early post-dose bronchodilation (from Day1), dyspnoea, symptoms and activities, without adversely affecting safety and tolerability.